The use of the Classic and Modified Transfer of the Lower Trapezius Muscle (Elhassan Transfer) as a Primary or Secondary Method for Surgical Reconstruction of the Abduction and External Rotation of the Shoulder in Brachial Plexus Injury - Hatskyi, O.O.; Tretiak, I.B.; Tsymbaliuk, V.I.; Tsymbaliuk, Ya.V.; Hao, Jiang (TERRA ORTHOPAEDICA, 2023)
Background. Brachial plexus injury (BPI) leads to severe dysfunction of the upper extremity (UE). Elbow flexion and multiaxial movements in glenohumeral joint (MGHJ) are prioritized in reconstruction strategy. Time-dependent (< 6 months) nerve transfers (NT) allow effective restoring of MGHJ. Late (> 6 months) reconstruction of MGHJ remains completely dependent on transfers of the functional tendon-muscle complexes. Objective: to compare the outcomes of the classic Elhassan (c) and modified (m) transfer of the lower trapezius muscle (LTT) on recovery of monoaxial MGHJ. Materials and Methods. Patient (P.) #3 with M4+ recovery of the deltoid muscle (DM) after NT and P. #4 without spontaneous recovery (SR) of DM – forward flexion (FF) was 170° and 0°, respectively, received cLTT. Patient #1 with M4+ recovery of DM after NT and P. #2 with M4+ SR of DM (FF was 160° and 50°, respectively), received mLTT – distal fixation point has been changed from the tendon of the infraspinatus to the tendon of supraspinatus muscle. Results. Shoulder abduction (ABD) has been restored to 50° in P. #1 and P. #2, while the recovery of the external rotation (ER) has not been achieved – upper arm remained internally rotated (IR). ABD has been restored to 40° and 80° in P. #3 and P. #4; simultaneously +15° and +70° of ER has been restored. Conclusions. The use of mLTT leads to more effective recovery of monoaxial MGHJ – ABD – 50° vs. 40° after cLTT. The use of cLTT leads to more effective recovery of another monoaxial MGHJ – ER – +15° and +70° vs. IR after mLTT; LTT should only be considered as a complementary surgical procedure, which utilization should cohere with a patient’s requirements to the MGHJ.